LIS Program Representatives’ Perspectives on Preparing Students for Careers in Research Data Management and Data-Related Librarianship - Jennifer Abel; Alisa B. Rod (Evidence Based Library and Information Practice)
Objective – This study aims to contribute a qualitative analysis of the perspectives of LIS program representatives on providing research data management (RDM) and data librarianship training opportunities to their students. The primary objectives of the study are to determine which programs currently provide training opportunities for students in RDM and related areas, as well as whether programs have provided such opportunities in the past and/or intend to do so in the future.